2022
DOI: 10.1002/cptc.202100289
|View full text |Cite
|
Sign up to set email alerts
|

Using Fiber Bragg Grating Sensors to Quantify Temperature Non‐Uniformities in Plasmonic Catalyst Beds under Illumination

Abstract: Distinguishing between photothermal and non‐thermal contributions is essential in plasmon catalysis. Use of a tailored optical temperature sensor based on fiber Bragg gratings enabled us to obtain an accurate temperature map of an illuminated plasmonic catalyst bed with high spatiotemporal resolution. Its importance for quantification of the photothermal and non‐thermal contributions to plasmon catalysis is demonstrated using a Ru/Al2O3 catalyst. Upon illumination with LEDs, we measured temperature differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…They observed that the activity of the catalyst upon sunlight illumination increased superlinearly with a higher loading of metal in the catalyst. This effect was attributed to collective photothermal heating, which was further supported by continuous flow experiments [34] and multipoint temperature measurements inside the illuminated catalyst bed [35].…”
Section: Introductionmentioning
confidence: 63%
“…They observed that the activity of the catalyst upon sunlight illumination increased superlinearly with a higher loading of metal in the catalyst. This effect was attributed to collective photothermal heating, which was further supported by continuous flow experiments [34] and multipoint temperature measurements inside the illuminated catalyst bed [35].…”
Section: Introductionmentioning
confidence: 63%
“…In particular, the sample in ref. 51 consisted mostly of high-emissivity alumina (in contrast to ref. 17 where the amount of alumina was small and instead the sample consisted of additional materials with lower emissivities; see discussion in ref.…”
Section: Contribution Of Thermal Emission To the Photothermal Nonline...mentioning
confidence: 83%
“…In contrast to these experiments which were characterized by low-emissivity samples, a recent experimental work 51 employed a high-emissivity sample. In particular, the sample in ref.…”
Section: Contribution Of Thermal Emission To the Photothermal Nonline...mentioning
confidence: 99%
See 2 more Smart Citations